A Phenomenological Study on the Reintegrating Experiences of Prison Torture Survivors into the Community in Gondar, Ethiopia - Sharew, Adebababy (The prison journal, 2024)
This phenomenological study explores the reintegrating experiences of nine prison torture survivors in the community of Gondar, Ethiopia. Data were collected through in-depth interviews and then thematically analyzed, revealing three major themes: the nature of reintegration, personal challenges of integration, and available supports for reintegration. The findings revealed prison torture survivors’ successful integration was based on their community social bonds. Poorly reintegrated prison torture survivors gradually become violent and committed other crimes. Providing community-based psychosocial support and well-organized social services is necessary for the well-being and sustainable reintegration of prison torture survivors into the community.